Action learning sets and social capital: ameliorating the burden of clergy isolation in one rural diocese. (1st September 2016) - Muskett, Judith A.; Village, Andrew
ABSTRACT: Rural clergy often lack colleagues and may struggle with isolation, especially if over-extended in multi-parish benefices. Theory suggests that this sense of isolation could be addressed by launching clergy action learning sets, which have the potential to establish a peer support network through the formation of social capital as a by-product of the pedagogical process. This case study looks at the effect of action learning set membership upon clergy involved in a new ministry development programme in one rural Church of England diocese. Markers of social capital (networks, norms and social trust) were found among set members, some of whom were prepared to draw on the new resource for assistance with problems, while others were ready to support such colleagues. Pre-existing support networks were one reason for clergy not intending to capitalize on the new links; another was the geographically dispersed set memberships. Geography may militate against exploiting social capital, but a distance of many miles between priest and trusted confidant can be advantageous. The study demonstrates that the notion that social capital formed through action learning will ameliorate isolation among some geographically scattered clergy is grounded not only in theory but also in practice.